The Assessment of Phase of Preschool Language: Applying the language benchmarks framework to characterize language profiles and change in four- to five-year-olds with autism spectrum disorder. (July 2019) - Flanagan, Helen E; Smith, Isabel M; Davidson, Fiona
Background and aims: We introduce the Assessment of Phase of Preschool Language (APPL), a rating form that characterizes children's language according to a well-established framework recommended by Tager-Flusberg et al. (2009). The language benchmarks framework defines children's language as falling at one of the Pre-verbal, First Words, Word Combinations, Sentences, or Complex Language phases for phonology, vocabulary, grammar, pragmatics, and overall language. The APPL is a flexible assessment tool that allows assessors to determine language phase using a range of assessment sources: natural language samples, standardized measures, and/or parent rating forms. Using the APPL, we examined language profiles in four- and five-year-olds with autism spectrum disorder and explored language development during a community-based Naturalistic Developmental Behavioral Intervention program. Methods: Community speech-language pathologists completed the APPL with 95 four- and five-year-olds at the beginning of the treatment. The APPL was re-administered after a mean of 10 months of intervention (SD = 2 months) for 46 of these children. Children received treatment for up to 15 h per week in their homes and/or community childcare centers. Pivotal Response Treatment was the main form of intervention. The Picture Exchange Communication System or other augmentative and alternative communication systems were also used with many pre-verbal children. Results: At the beginning of intervention, the most common language phase was Word Combinations (44%), followed by Pre-verbal (26%), Sentences (20%), and then First Words (10%). Only 24% of children had even profiles (i.e. phonology, vocabulary, grammar, and pragmatics skills at the same level). Phonology was a common area of relative strength, and pragmatics was a common area of relative weakness. Ten months of intervention was associated with gains in overall language phase for 37% of children. Approximately half gained at least one phase in Grammar (57%), Vocabulary (51%), and Phonology (46%), while Pragmatics improved for 33%. Gains varied based on initial language phase. Inclusion of skills using augmentative and alternative communication enhanced interpretation of change during intervention. Conclusions: Four- and five-year-olds with autism spectrum disorder in this sample tended to have uneven skills across expressive language domains. Community-based Naturalistic Developmental Behavioral Intervention was associated with gains in language phase in older preschoolers with autism spectrum disorder. Gains varied across language domains and were influenced by initial language phase. Implications: The Assessment of Phase of Preschool Language is a useful tool to support consistent application of the language benchmarks framework. It is important to consider all language domains when characterizing language skills and treatment impact in children with autism spectrum disorder.